If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 3) = 2(5x + -2) + 6 Reorder the terms: 4(3 + 2x) = 2(5x + -2) + 6 (3 * 4 + 2x * 4) = 2(5x + -2) + 6 (12 + 8x) = 2(5x + -2) + 6 Reorder the terms: 12 + 8x = 2(-2 + 5x) + 6 12 + 8x = (-2 * 2 + 5x * 2) + 6 12 + 8x = (-4 + 10x) + 6 Reorder the terms: 12 + 8x = -4 + 6 + 10x Combine like terms: -4 + 6 = 2 12 + 8x = 2 + 10x Solving 12 + 8x = 2 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 12 + 8x + -10x = 2 + 10x + -10x Combine like terms: 8x + -10x = -2x 12 + -2x = 2 + 10x + -10x Combine like terms: 10x + -10x = 0 12 + -2x = 2 + 0 12 + -2x = 2 Add '-12' to each side of the equation. 12 + -12 + -2x = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 2 + -12 -2x = 2 + -12 Combine like terms: 2 + -12 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| 9-6y=24-8y+7 | | 3t^2=6t-12 | | 4y-7+2y=5y-6+9 | | 13-2x= | | x-5y=3v | | 2x+5=3x+10 | | 3a-4=A | | 2x-20=5x-5 | | 189-5x=31x+17 | | -35-4x=13-10x | | 51-3x=7x+21 | | 6x+14=91-5x | | 6x+36=14x-52 | | (6x-5)(6x-5)=36x-25 | | 2a+2b+2c=262 | | 2n-20=7n | | 6x^2-10x+1=0 | | 19-3=x-8 | | 54x+15=16 | | 4=3x-10+x-2 | | 15-6(2x-5)=50 | | -7x-12=-3x-16 | | 3x+3=5x-11 | | x+12=5x-16 | | 24-5y=3(10-y) | | -x^4+13x^2-3=0 | | x^3-2x^2-5x+6=0 | | x+5x=63 | | 5x=1535 | | 2x+6=-1 | | 120+2x=118 | | 7x^2-3=4 |